Alleviating 3-MCPD-induced male reproductive toxicity: Mechanistic insights and resveratrol intervention - Kai-Lee Wang; Yi-Fen Chiang; Ko-Chieh Huang; Hsin-Yuan Chen; Mohamed Ali; Shih-Min Hsia (Ecotoxicology and Environmental Safety, 2024)
3-Monochloropropane-1, 2-diol (3-MCPD), a food-borne contaminant, is widely regarded as the primary cause of male infertility. At present, identifying a method to improve/reduce the male reproductive toxicity caused by 3-MCPD is important. In our study, we explored the potential application of resveratrol (RSV) in mitigating the adverse effects of 3-MCPD. Using 7-week-old Sprague-Dawley (SD) rats as animal models, we investigated the impacts and underlying mechanisms of 3-MCPD and RSV on reproductive function. The administration of 3-MCPD led to significant reductions in testicular and epididymal weights, as well as disruptions in spermatogenesis and histological abnormalities. However, co-treatment with RSV and 3-MCPD mitigated these adverse effects. In vitro study, RSV exhibited the ability to reverse the decline in Leydig and Sertoli cell populations inflicted by 3-MCPD treatment. Mechanistically, RSV reduced endoplasmic reticulum stress (PARP), inflammasome activation (NLRP3), and autophagy-mediated lysosome dysfunction (p62 and LC3BII) induced by 3-MCPD. In addition, 3-MCPD treatment increased the expression level of steroidogenesis-related proteins, steroidogenic acute regulatory (StAR) and CYP11A1, but RSV normalized StAR expression. Moreover, 3-MCPD-induced pro-inflammatory responses were counteracted by RSV treatment, with the cytokine reduction and modulation of CD206 expression, a marker of macrophage activation. These findings indicate that RSV attenuates 3-MCPD-induced reproductive toxicity, highlighting its application potential as an adjuvant agent for male reproductive health.